Development of Author’s Invoices and Their Use in Design Projects of Modern Clothing - Hryhorova, larysa (Professional Art Education, 2021)
The purpose of the article is to consider the role of copyright textures in the design of modern clothes; analyze the collections of students of the department of Design of the H.S. Skovoroda Kharkov National Pedagogical University from the point of view of the development of textured surface and use in the creation of a suit. Methods & methodology. We used such research methods as subject-analytical for studying literary and illustrative sources; a terminological method for an unambiguous understanding of the essential features of design; psychological method for verbal determination of the nature of the visual sensation from the tissue surface; to reveal the dependence of expressive means when creating textures. Scientific novelty is determined by the need to develop new versions of copyright textures and use them in the of modern clothing also due to the objective public need for multifunctional and specific expressive clothing that would satisfy the utilitarian and aesthetic needs of a person. Results. The theme of the surface of the material in the design of clothing is very relevant and requires constant innovative development to obtain new textural solutions. In modern design, the textures actively influences the stale of shaping the plastic, composition and the silhouette of the suit and also focuses on certain parts of the product. The role of texture in the implementation of the function of the suit and its influence on the person’s visual perception is considered studied techniques and ways to create a textured surface. In one model, you can combine various textured surfaces. This makes it possible to achieve a variety of solutions in creating a costume. To create textured surfaces, various manufacturing techniques are used, namely: the use of contrasting and nuanced combinations of textures; the use of traditional embroidery in combination with patchwork; quilting; embroidery; perforation; stitches and sewing elements; tucks and formation of folds; stretching, friction, stamping; drawing volumetric drawings and a photogram; saturation of the texture with volumetric additions (pile, knots, boucle, stones, brushes, plaits). Much attention is paid to the analysis of the works of students of the design department, focused on innovative development of textured surfaces and use when creating collections. Conclusions and practical significance. Analysis of ways to create copyright invoices based on the work of students of the Department of Design of H.S. Skovoroda Kharkov National Pedagogical University allows deeper rethinking of the influence of textured surfaces for the realization of design ideas, namely: the expressiveness of the image and compositional decision, the degree of bulkiness of clothing and mass density.